Inflation and Growth in Transition : Are the Asian Economies Different? - Sloek, Torsten (IMF Working Papers; Working Paper ;, 1999)
This paper examines the progress made in four Asian transition economies-China, Lao P.D.R., Vietnam, and Mongolia-to market-based systems. Overall, these economies appear to have had a more favorable experience with inflation stabilization and output growth than that of transition economies elsewhere. While initial conditions played an important role in determining the strategy and speed of the transition, growth performance benefited from continued macroeconomic stability and reforms in a key sector (such as agriculture); this confirms the need for sustained and rapid structural reforms and highlights the constraints for sustainable growth posed by weak financial and enterprise sectors.